A portable magnet for radiation biology and dosimetry studies in magnetic fields. Issue 3 (28th January 2022) - Causer, Trent J.; Rosenfeld, Anatoly B.; Metcalfe, Peter E.; Oborn, Bradley M.
Abstract: Background and Purpose: In the current and rapidly evolving era of real‐time MRI‐guided radiotherapy, our radiation biology and dosimetry knowledge is being tested in a novel way. This paper presents the successful design and implementation of a portable device used to generate strong localized magnetic fields. These are ideally suited for small‐scale experiments that mimic the magnetic field environment inside an MRI‐linac system, or more broadly MRI‐guided particle therapy as well. Materials and Methods: A portable permanent magnet‐based device employing an adjustable steel yoke and magnetic field focusing cones has been designed, constructed, and tested. The apparatus utilizes two banks of Nd 2 _2 Fe 14 _14 B permanent magnets totaling around 50 kg in mass to generate a strong magnetic field throughout a small volume between two pole tips. The yoke design allows adjustment of the pole tip gap and exchanging of the focusing cones. Further to this, beam portal holes are present in the yoke and focusing cones, allowing for radiation beams of up to 5 × × 5 cm 2 ^2 to pass through the region of high magnetic field between the focusing cone tips. Finite element magnetic modeling was performed to design and characterize the performance of the device. Automated physical measurements of the magnetic field components at various locations were measured to confirm the performance. The adjustable pole gap and interchangeable cones allows rapid changing of the experimental set‐up to allow different styles of measurements to be performed. Results: A mostly uniform magnetic field of 1.2 T can be achieved over a volume of at least 3 × × 3 × × 3 cm 3 ^3 . This can be reduced in strength to 0.3 T but increased in volume to 10 × × 10 × × 10 cm 3 ^3 via removal of the cone tips and/or adjustment of the steel yoke. Although small, these volumes are sufficient to house radiation detectors, cell culture dishes, and various phantom arrangements targeted at examining small radiation field dosimetry inside magnetic field strengths that can be changed with ease. Most important is the ability to align the magnetic field both perpendicular to, or inline with, the radiation beam. To date, the system has been successfully used to conduct published research in the areas of radiation detector performance, lung phantom dosimetry, and how small clinical electron beams behave in these strong magnetic fields. Conclusions: A portable, relatively inexpensive, and simple to operate device has successfully been constructed and used for performing radiation oncology studies around the theme of MRI‐guided radiotherapy. This can be in either inline and perpendicular magnetic fields of up to 1.2 T with x‐ray and particle beams.